Reasonable Irrationality: the Role of Reasons in the Diffusion of Pseudoscience - Blancke, Stefaan (Journal of cognition and culture, 2019)
Pseudoscience spreads through communicative and inferential processes that make people vulnerable to weird beliefs. However, the fact that pseudoscientific beliefs are unsubstantiated and have no basis in reality does not mean that the people who hold them have no reasons for doing so. We propose that, reasons play a central role in the diffusion of pseudoscience. On the basis of cultural epidemiology and the interactionist theory of reasoning, we will here analyse the structure and the function of reasons in the propagation of pseudoscience. We conclude by discussing the implications of our approach for the understanding of human irrationality.